2019
DOI: 10.1038/s41525-019-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Fetal sex determination in twin pregnancies using non-invasive prenatal testing

Abstract: Non-invasive prenatal testing (NIPT) is accurate for fetal sex determination in singleton pregnancies, but its accuracy is not well established in twin pregnancies. Here, we present an accurate sex prediction model to discriminate fetal sex in both dichorionic diamniotic (DCDA) and monochorionic diamniotic/monochorionic monoamniotic (MCDA/MCMA) twin pregnancies. A retrospective analysis was performed using a total of 198 twin pregnancies with documented sex. The prediction was based on a multinomial logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…Based on prior studies [ 3 , 9 ] and limited cases from the current study, singleton gestations affected with aneuploidy appear to be a suitable proxy for twin gestations in which both fetuses are affected with aneuploidy, either because the pregnancy is monochorionic, or because both placentas in a dichorionic gestation are impacted by the same aneuploidy. For trisomy 21, there was no significant difference noted between the MRs of affected singleton gestations and twin gestations in which both fetuses were affected.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Based on prior studies [ 3 , 9 ] and limited cases from the current study, singleton gestations affected with aneuploidy appear to be a suitable proxy for twin gestations in which both fetuses are affected with aneuploidy, either because the pregnancy is monochorionic, or because both placentas in a dichorionic gestation are impacted by the same aneuploidy. For trisomy 21, there was no significant difference noted between the MRs of affected singleton gestations and twin gestations in which both fetuses were affected.…”
Section: Discussionmentioning
confidence: 88%
“…This singleton group was assembled to biologically mimic the scenario of affected monochorionic twins. Both singleton gestations and monochorionic twins involve cfDNA analysis from a single placenta, and prior studies have demonstrated that monochorionic twin pregnancies behave similarly to singletons in the context of cfDNA screening [ 3 , 9 ]. By extension, in the rare circumstance that both placentas of a dichorionic pregnancy are affected with the same, non-mosaic aneuploidy (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, in the prediction of monogenic disease, the FF is also a key parameter 5,6 to determine the statistical thresholds to ensure the statistical significance. Lastly, when FF is accurately known, a more powerful test to screen for fetal trisomy can be developed 28,33 and the fetal sex determination in twin pregnancies 34,35 also becomes a much simpler problem. The ability of measuring FF with high accuracy would make LDFF serve as a valuable tool to improve NIPT performance.…”
Section: Discussionmentioning
confidence: 99%
“…Villela et al employed NIPT for sex determination in twin pregnancies. Their analytical method exhibited 100% sensitivity and specificity when both twins were female, while the presence of a male co-twin declined the sensitivity and specificity to 98 and 95%, respectively [4]. More recently, Yang et al successfully applied NIPT for screening more than 400 twin pregnancies including both double chorionic dichorionic diamniotic (DCDA) and monochorionic diamniotic (MCDA).…”
Section: Introductionmentioning
confidence: 99%